2005
DOI: 10.1590/s0006-87052005000400008
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade do cafeeiro e cultivos intercalares sob diferentes regimes hídricos

Abstract: RESUMOO efeito de diferentes regimes hídricos na produtividade do cafeeiro e cultivos intercalares foi determinado em um experimento em Latossolo Vermelho distroférrico, em Londrina, PR, durante sete anos. Os tratamentos consistiram de aplicação de irrigação para manter a camada de solo de 0,7 m com mais de 50% da água disponível (40 kPa a 0,25 m) e 30% de água disponível (70 kPa a 0,25 m), além de um tratamento não irrigado. Após o terceiro ano de implantação da lavoura, na fase reprodutiva do cafeeiro, a cam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 4 publications
0
4
0
4
Order By: Relevance
“…During cultivation of perennial species such as coffee, the initial soil and water conditions are critical for growth and establishment of a healthy plant in addition to obtaining high yields (Dias et al, 2007;Faria and Siqueira, 2005;Fialho et al, 2010;Serafim et al, 2013a). For instance, when a conventional management system that uses shallow furrows and where the soil is superficially chemically amended, the root system stays shallow in the first 2 years.…”
Section: Introductionmentioning
confidence: 99%
“…During cultivation of perennial species such as coffee, the initial soil and water conditions are critical for growth and establishment of a healthy plant in addition to obtaining high yields (Dias et al, 2007;Faria and Siqueira, 2005;Fialho et al, 2010;Serafim et al, 2013a). For instance, when a conventional management system that uses shallow furrows and where the soil is superficially chemically amended, the root system stays shallow in the first 2 years.…”
Section: Introductionmentioning
confidence: 99%
“…The studies conducted by these authors and others like SILVA et al (2002), SILVA et al (2003b, SILVA (2005) andGOMES et al (2007) have demonstrated that irrigation did not prevent the effect of biennial culture, but helped to reduce it since the results indicated that the fall in productivity in irrigated treatments was not as sharp as in non-irrigated treatment. However, SILVA et al (2008) andSIQUEIRA (2005) found that irrigation failed to attenuate the effects of biennial culture. Establish comparisons of productivity and biennial crop, between experiments, are complex since factors such as cultivar, crop management and weather conditions may be differentiated and influence the performance of the crop.…”
Section: Resultsmentioning
confidence: 99%
“…One of the few studies that related the matric potential to critical soil moisture for coffee crop was developed by FARIA & SIQUEIRA (2005) who found the threshold -40 kPa, as the one associated with the best response in crop yield. However, FARIA et al (2009) observed tensions values that varied among treatments from -11 to -33 kPa indicating differences occurred in water absorption among the treatments between irrigations.…”
Section: Introductionmentioning
confidence: 99%